2019
DOI: 10.1021/acsami.9b15896
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Biocompatible Hydrogels from Cellulose Nanocrystals for Locally Targeted Sustained Drug Release

Abstract: Injectable hydrogels from biocompatible materials are in demand for tissue engineering and drug delivery systems. Here, we produce hydrogels from mere cellulose nanocrystals (CNCs) by salt-induced charge screening. The injectability of CNC hydrogels was assessed by a combination of shear and capillary rheology, revealing that CNC hydrogels are conveyed via plug flow in capillaries allowing injection with minimal impact on mechanical properties. The potential of CNC hydrogels as drug carriers was elaborated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…Plots of Figure 4 show that at a pH of 2 there is no vitamin delivered. When the pH is changed to 7, the structure of the BNC web is opened, allowing for delivery [ 39 ]. This also confirms that we can modulate the release of the vitamins with a change in the pH conditions, which is related to the trajectory that this would follow in normal digestion.…”
Section: Resultsmentioning
confidence: 99%
“…Plots of Figure 4 show that at a pH of 2 there is no vitamin delivered. When the pH is changed to 7, the structure of the BNC web is opened, allowing for delivery [ 39 ]. This also confirms that we can modulate the release of the vitamins with a change in the pH conditions, which is related to the trajectory that this would follow in normal digestion.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that collagen [157], hydrogel [158,159], or mineral [160] carriers of antibiotics and non-antibiotic agents (e.g., chitosan, antimicrobial peptides) are quite effective in vitro and even in vivo. However, the evidence for using such alternative antimicrobial carriers in preventing PJI remains to be demonstrated in clinical studies.…”
Section: Systemic/local Antibioticsmentioning
confidence: 99%
“…[123] Some recent studies have applied supramolecular methods for generating injectable hydrogels for pH-triggered drug delivery. [106,[124][125][126] Supramolecular hydrogels are usually fabricated by crosslinking polymers with supramolecular noncovalent interactions, including hydrophobic or ionic interactions, inclusion complexation, or metal-ligand coordination. These hydrogels are stimuli responsive, injectable, have excellent biocompatibility, and can be loaded with bioactive molecules and proteins.…”
Section: Ph-responsive Injectable Hydrogels For Controlled and Local mentioning
confidence: 99%